Structures of Legal Competences - Sieckmann, Jan-Reinard (Springer Science and Business Media B.V., 2023)
A legal or, more generally, normative competence might be understood as the power to change the normative situation according to one’s will. Competence norms are norms that confer such a power to a particular agent, of course with certain conditions. Several doubts remain: Must there be a change, or might the use of a competence merely confirm the existing normative situation, however, creating an independent normative reason?Must the will to determine the normative situation be the reason for recognizing a certain norm as valid, or might it be only a circumstance that figures in the justification of this norm?Does the exercise of a competence create an object that otherwise would not exist, or does it define the validity of a norm? On the other hand, it is clear that competences are not merely permissions. But what are the relations between competence and permission? Can the exercise of a competence be completely prohibited, or must it in some sense be permitted? And how does the notion of a competence relate to the distinction of definitive norms and norms that are valid only in principle?
CRIS-Team Scopus Importer:2024-12-16
Keywords: Argument; Balancing; Competence; Intention; Legal change; Permission; Validity